Population Pharmacokinetic Modeling of the Oral Calcitonin Gene‐Related Peptide Receptor Antagonist Rimegepant in Adults - Craig M. Comisar; Jim H. Hughes; Jose Francis; Yorinao Chinda; Yamato Sano; Chieko Muto; Christine Neumar; Rajinder Bhardwaj; Richard Bertz; Jing Liu (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Rimegepant is a small‐molecule calcitonin gene‐related peptide receptor antagonist approved for acute and preventive migraine treatment in adults, administered as an orally disintegrating tablet (ODT). A population pharmacokinetic analysis was performed to describe rimegepant's plasma concentration‐time course and to estimate covariate effects on rimegepant exposure. The model was developed/evaluated in 3 stages using data from 11 phase 1 clinical studies, wherein rimegepant was administered orally to healthy adults, elderly people with stable chronic illness(es), adults with renal or hepatic dysfunction, and healthy adults with Japanese or Chinese ethnicity. Plasma concentration‐time data were analyzed using nonlinear mixed effects modeling. A 2‐compartment model with 4 transit compartments and a first‐order absorption best described the rimegepant plasma concentration‐time course. Estimated typical values (%relative standard error) were apparent clearance (CL/F) = 24.1 L/h (4.86%), apparent central volume of distribution (Vc/F) = 114.0 L (5.36%), apparent inter‐compartmental clearance (Q/F) = 3.94 L/h (6.37%), apparent peripheral volume of distribution (Vp/F) = 46.0 L (5.30%), absorption rate constant (ka) = 3.86 h−1 (28.4%), and transit absorption rate constant (ktr) = 8.23 h−1 (8.24%). Statistically significant covariates included empirical allometric body weight‐based scaling exponents (0.75 for CL/F and Q/F and 1 for Vc/F and Vp/F); severe/moderate hepatic impairment and fluconazole/itraconazole co‐administration on CL/F; fed status, dose on relative bioavailability; and fed status, itraconazole co‐administration, and capsule and ODT formulations on transition absorption rate constant. Only severe hepatic impairment and co‐administration of itraconazole resulted in a clinically significant decrease in rimegepant CL/F, supporting the recommendation to avoid rimegepant administration in patients with severe hepatic impairment or with a strong CYP3A4 inhibitor.